What can 7T sodium MRI tell us about cellular energy depletion and neurotransmission in Alzheimer's disease?. Issue 11 (2nd December 2021) - Haeger, Alexa; Bottlaender, Michel; Lagarde, Julien; Porciuncula Baptista, Renata; Rabrait‐Lerman, Cécile; Luecken, Volker; Schulz, Jörg B.; Vignaud, Alexandre; Sarazin, Marie; Reetz, Kathrin; Romanzetti, Sandro; Boumezbeur, Fawzi
Abstract: The pathophysiological processes underlying the development and progression of Alzheimer's disease (AD) on the neuronal level are still unclear. Previous research has hinted at metabolic energy deficits and altered sodium homeostasis with impaired neuronal function as a potential metabolic marker relevant for neurotransmission in AD. Using sodium ( 23 Na) magnetic resonance (MR) imaging on an ultra‐high‐field 7 Tesla MR scanner, we found increased cerebral tissue sodium concentration (TSC) in 17 biomarker‐defined AD patients compared to 22 age‐matched control subjects in vivo. TSC was highly discriminative between controls and early AD stages and was predictive for cognitive state, and associated with regional tau load assessed with flortaucipir‐positron emission tomography as a possible mediator of TSC‐associated neurodegeneration. TSC could therefore serve as a non‐invasive, stage‐dependent, metabolic imaging marker. Setting a focus on cellular metabolism and potentially disturbed interneuronal communication due to energy‐dependent altered cell homeostasis could hamper progressive cognitive decline by targeting these processes in future interventions.